Pengaruh Kepribadian, Work Life Balance dan Budaya Organisasi terhadap Kinerja Pegawai Pada Kantor Kelurahan Penatih (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The Penatih Subdistrict Office has responsibility for implementing public services to the community, however in its realization public services in the Penatih Subdistrict Environment have not been able to reach the target percentage that has been set. This is caused by the employee's lack of personality, the adequacy between the employee's work and personal life, and the employee's lack of understanding of the village's values and goals. The aim of the research is to determine the influence of personality, work balance and organizational culture on employee performance at the Penatih District Office. The population in this study were all employees at the Penatih Village Office. The sample in the research was determined using a saturated sampling method, so the total sample was 35 employees. Based on the results of data analysis, it is concluded that personality partially has a significant positive effect on employee performance, work life balance partially has a significant positive effect on employee performance, organizational culture partially has a significant positive effect on employee performance, and personality, work life balance and organizational culture simultaneously significant positive effect on employee performance.